The Analysis of Dangerous Face-Cream Cosmetic Product Threats and Preventive Strategies - Anggraini, Shinta (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
Cosmetics have now transformed into one of the daily necessities and are consumed by all demographics, both young and old, men and women. The increase in demand and need for cosmetic products was initially only for beauty purposes, but it has since evolved to include health, body care, and hygiene needs, culminating in the current trend of smooth and flawless skin, commonly known as glass skin, using a series of specific facial cream cosmetic products. The increase in public demand for facial cream cosmetic products presents an opportunity for threats to human security, where cosmetics manufacturer seek maximum profit by adding several hazardous substances, thereby posing a risk to public health. This research was conducted using qualitative research methods with data collection techniques from interviews, observations, and library research. The research results indicate a serious threat from dangerous facial cream cosmetic products with various evolving modes that 'outsmart' regulations, actions carried out by individuals who possess facilities, capital, knowledge, and access related to these matters. Therefore, it is necessary to formulate appropriate strategies to prevent strategic surprises through scenario planning that outlines several intelligence strategies to prevent and anticipate them.